The Dynamics, Rituals, and Chinese Identity at Tjoe Tik Kiong Temple (慈德宫, Cí dé gōng), Pasuruan-Indonesia - Olivia Olivia; Toetik Koerbadiati; Dede Oetomo (k@ta: A Biannual Publication on the Study of Language and Literature, 2025)
This paper examines how the Tjoe Tik Kiong Temple in Pasuruan, Indonesia, was a reinvention of the MaZu pilgrimage and how the Pasuruan Chinese have preserved the Mazu Belief to the present day. The Tjoe Tik Kiong Temple in Pasuruan, Indonesia, has more than a hundred years of history. During the Soeharto presidency, the Indonesian Chinese were subject to many restrictions that altered the ceremonial activities of the traditional Mazu belief. However, after 2000, many local Chinese temples started reorganizing the pilgrimage activities, and the believers in Pasuruan City are no exception. This study used a field survey to collect the first data, including direct participation in the pilgrimage activities and interviews with temple committees and worshippers. The results of this study show that after more than three decades of restrictions, many young Chinese no longer speak Chinese, which allows for different rituals to be practiced as well as different rituals for traditional Mazu Beliefs. This study demonstrates that although there are some differences, the Mazu Belief and pilgrimage contribute to identifying Chinese Indonesian identity.